365 Days > 366 Days: The (in)Ability to Earn Good Time Credit During the Time of COVID-19 - Craun, Sarah W. (The prison journal, 2023)
Federal offenders sentenced to imprisonment for more than a year may earn “good time credit”. Offenders sentenced to 365 days are ineligible for this potential sentence reduction of up to 54 days a year. Using 2020 through 2022 data from the United States Sentencing Commission, we identified 3,765 federal offenders sentenced to either 365- or 366-days’ imprisonment. Independent variables included offender, legal, and case characteristics. Integrating the COVID-19 pandemic, we reviewed the percentage of compassionate release motions granted at the district level. A hierarchical logistic regression with random effects illustrated several measures connected to the ability to earn goodtime credit.